Estudio de impacto ambiental del proyecto minero, "nicomar", en el sector corral quemado, distrito de magdalena, cajamarca. - Juarez Aredo, Nehemias (2015)
The present study aims to develop an Environmental Impact Study in order to exploit and benefit limestone. The environmental management tool developed in Corral Quemado sector in the district of Magdalena, Province of Cajamarca, department of Cajamarca. In order to justify the project, identified and studied the quality of the ore, in order to establish the development of the Environmental Impact Study. To begin preparing the Environmental Impact Study description of the physical, biological, economic and social environment of the area where it will develop the Project was Nicomar. As a second step, it described in detail the steps and operations to be performed with this information identifies and assesses the impacts that will be generated by the project. Last step, and after a detailed study and analysis of the first two, the Environmental Management Plan, in order to prevent, mitigate and correct the negative environmental impacts, also intends to propose a monitoring plan and a Plan closing for proper and consistent monitoring of the parameters that have been identified as might be affected, and ensure the rehabilitation of disturbed areas, returning them as possible to its initial conditions. Because of the characteristics of the physical, biological, economic, social environment and proper implementation of the Environmental Management Plan, the Nicomar Project will develop causing mild and moderate environmental impacts mostly; vast and sufficient information indicates that the project is environmentally viable.